Land clearing in south-eastern Australia: Drivers, policy effects and implications for the future. (March 2021) - Heagney, E.C.; Falster, D.S.; Kovač, M.
Highlights: Summarises 25 years of land clearing trends in south-eastern Australia and assesses the efficacy of policy interventions over that period. ○ Uses an information theoretic approach to compare and assess alternate hypotheses regarding the pro ximate drivers of land clearing. Uses econometric modelling, including stationarity testing and investigation of Granger and Heckman causality to avoid spurious correlations. Identifies market variables as key drivers of clearing in this context, and shows that outcomes from policy interventions are very limited. Points to the need for better integration with agricultural policy. Abstract: This paper aims to provide clarity around why land clearing occurs in a developed world context. We apply an information theoretic approach to discriminate amongst alternative hypotheses of the proximate drivers of land clearing, and test their capacity to explain historical rates of land clearing in New South Wales, a state in south-eastern Australia, between 1990 and 2017. We also assess the efficacy of policy interventions in NSW to date and discuss how lessons learned from the Australian experience might best be harnessed for effective policy design in Australia and beyond. Our results indicate that farmers in NSW clear land in response to economic opportunities presented by favourable market signals. We identify a particular focus on potential revenues, whereby high agricultural commodity prices encourage agricultural expansion and an associated loss of on-farm vegetation. Our results indicate that, to date, direct regulation is likely to have had an impact in only one of the three regions modelled. We conclude that better integration with agricultural policy, including careful examination the effects of agricultural subsidies, will be required to ensure that increasing global food demand does not drive further forest loss in major food exporting nations like Australia.